A nationally representative One Health multi-pathogen serosurvey in Cambodia: study protocol for the RACSMEI mixed-methods study - Andrea Antoniolli; Erik Karlsson; Tephanie Sieng; Sébastien Boyer; Michael White; Sokleaph Cheng; Hélène Guis; Sidonn Krang; Sopheak Sorn; Malen Chan; Sophea Iv; Sitha Sin; et al. (BMC Infectious Diseases, 2026)
Abstract Background Cambodia faces a high and complex burden of zoonotic, vector-borne, vaccine-preventable and environmentally transmitted infections, driven by intensive human–animal–environment interactions. However, nationally representative data integrating human, animal and environmental dimensions of pathogen exposure remain limited. The RACSMEI (Risk Assessment of Community Spread of Multiple Endemic Infectious Diseases in a One Health Perspective) study aims to address this gap through a nationwide One Health serosurvey designed to generate policy-relevant epidemiological evidence for precision public health and integrated surveillance. Methods/design RACSMEI is a nationwide, cross-sectional, mixed-methods study conducted across all 25 provinces of Cambodia. Using a stratified, multi-stage cluster sampling design, approximately 15,000 individuals aged 2–75 years will be enrolled from 4,160 households in 104 randomly selected villages. Human, animal (poultry, pigs, dogs, cattle, small ruminants, rodents) and environmental (water, soil, air, surface swabs) samples will be collected. Exposure to more than 50 endemic, emerging, vaccine-preventable and elimination-targeted pathogens will be assessed using multiplex serological assays, molecular diagnostics and metagenomics sequencing approaches. Quantitative surveys will be complemented by semi-structured interviews and focus group discussions to explore social, behavioural and health system determinants of infection risk and care-seeking behaviours. Analyses will account for the complex survey design and integrate epidemiological, environmental and social science data. Discussion By combining nationally representative sampling with integrated human, animal, environmental and social science data, RACSMEI aims to generate comprehensive evidence on infectious disease exposure and transmission risks across diverse socio-ecological contexts in Cambodia. The study will provide policy-relevant insights to support One Health surveillance strategies and targeted public health interventions. The protocol was approved by the Cambodian National Ethics Committee for Health Research and the Institutional Review Board of Institut Pasteur Paris. Trial registration The study is registered on ClinicalTrials.gov (NCT07358910). It was retrospectively registered on 14 January 2026.